Systemic risk and collateral adequacy: Evidence from the great crisis - Radoslav Raykov (Bank of Canada, 2019)
Conventional collateral requirements are highly conservative but are not explicitly designed to deal with systemic risk. This paper explores the adequacy of conventional collateral levels against systemic risk in the Canadian futures market during the 2008 crisis. Our results show that conventional collateral levels adequately absorb crisis-level systemic risk, even allowing for an implausibly large margin of error. However, this occurs at the expense of unequal buffering of systemic risk across banks. We document that the largest systemic risk contributors are buffered relatively less than the rest and that there is a large cross-country difference in the behavior of US and Canadian institutions. Nonetheless, even this does not result in meaningful risk spillovers. The maximum expected market shortfall in excess of collateral comes up to at most 1% of the banks' market capitalization, and hence the added systemic risk does not exceed the effect of a 1% downward stock price move.
Keywords: G10; G20; 330; Financial markets; Financial institutions